The drosophila KIF1A homolog unc-104 is important for site-specific synapse maturation - Zhang, Yao; Hannan, Shabab B.; Stapper, Zeenna A.; Kern, Jeannine V.; Jahn, Thomas R.; Rasse, Tobias M. (Frontiers in cellular neuroscience, 2016)
Mutations in the kinesin-3 family member KIF1A have been associated with hereditary spastic paraplegia (HSP), hereditary and sensory autonomic neuropathy type 2 (HSAN2) and non-syndromic intellectual disability (ID). Both autosomal recessive and autosomal dominant forms of inheritance have been reported. Loss of KIF1A or its homolog unc-104 causes early postnatal or embryonic lethality in mice and Drosophila, respectively. In this study, we use a previously described hypomorphic allele of unc-104, unc-104bris, to investigate the impact of partial loss-of-function of kinesin-3 on synapse maturation at the Drosophila neuromuscular junction (NMJ). Unc-104bris mutants exhibit structural defects where a subset of synapses at the NMJ lack all investigated active zone (AZ) proteins, suggesting a complete failure in the formation of the cytomatrix at the active zone (CAZ) at these sites. Modulating synaptic Bruchpilot (Brp) levels by ectopic overexpression or RNAi-mediated knockdown suggests that the loss of AZ components such as Ca2+ channels and Liprin-α is caused by impaired kinesin-3 based transport rather than due to the absence of the key AZ organizer protein, Brp. In addition to defects in CAZ assembly, unc-104bris mutants display further defects such as depletion of dense core and synaptic vesicle (SV) markers from the NMJ. Notably, the level of Rab3, which is important for the allocation of AZ proteins to individual release sites, was severely reduced at unc-104bris mutant NMJs. Overexpression of Rab3 partially ameliorates synaptic phenotypes of unc-104bris larvae, suggesting that lack of presynaptic Rab3 contributes to defects in synapse maturation.
Gesehen am 08.10.2021